Kubernetes patterns reusable elements for designing cloud native applications - Ibryam, Bilgin; Huss, Roland (O'Reilly Media, Inc., 2023)
The way developers design, build, and run software has changed significantly with the evolution of microservices and containers. These modern architectures offer new distributed primitives that require a different set of practices than many developers, tech leads, and architects are accustomed to. With this focused guide, Bilgin Ibryam and Roland Huss provide common reusable patterns and principles for designing and implementing cloud native applications on Kubernetes. Each pattern includes a description of the problem and a Kubernetes-specific solution. All patterns are backed by and demonstrated with concrete code examples. This updated edition is ideal for developers and architects familiar with basic Kubernetes concepts who want to learn how to solve common cloud native challenges with proven design patterns.
Includes bibliographical references and index
Keywords: Electronic data processing -- Distributed processing; Application software -- Development; Open source software; Cloud computing; Traitement réparti; Logiciels d'application; Développement; Logiciels libres; Infonuagique; Application software; Development; Electronic data processing; Distributed processing